Germacranolides from Mikania guaco - Rüngeler, Peter (2001)
Fourteen novel sesquiterpene lactones of the germacranolide type have been isolated from the aerial parts of Mikania guaco: six costunolide, two melampolide and six germacra-4-trans,10(14),11(13)-trien-12,6α-olide derivatives. Except for one compound all the others possess a carbonyl function at C-9. Eight were obtained in the form of four isomer pairs which were difficult to separate. Structure elucidation was based on mass and 1D and 2D NMR measurements. Low energy conformations were obtained by quantum mechanical calculations. Pyrrolizidine alkaloids could not be detected.